Systematic Review: Pengaruh Penggunaan Kosmetik Terhadap Kejadian Acne vulgaris - Suhartomi, Suhartomi; Panjaitan, Joice Sonya Gani; Syarifah, Siti; Marpaung, Okto Parningotan Elia (Nommensen Journal of Medicine, 2024)
Background: Several factors reported to be associated with the incidence of acne vulgaris include genetics, race, stress, diet, cosmetics, drugs, and smoking habits. Many studies have been performed to look for the effect of cosmetic use on the incidence of acne vulgaris, but these studies are still limited to observational studies. Therefore, this study aimed to analyze the effect of cosmetic use on the incidence and severity of acne vulgaris through several studies in the 2018-2023 period. Methods: This systematic review was performed by systematically searching for some literatures on Google Scholar with the keywords Cosmetics and Acne vulgaris. The results of this systematic searching found 21 scientific articles in either English or Indonesian. Results: The most of literatures obtained reported that the use of cosmetics, in the form of compact powder, BB cream, and foundation affected the incidence of acne vulgaris. Meanwhile, patients suffered from acne vulgaris, who used compact powder and foundation consistently aggravated acne vulgaris. There is still limited study on other decorative cosmetics such as concealers and primers on the incidence of acne vulgaris. Conclusion: The use of cosmetics such as compact powder, BB cream, and foundation can cause acne vulgaris, furthermore compact powder and foundation can also aggravate acne vulgaris that has occurred.